Neuropsychological changes related to unilateral lenticulostriate infarcts. Issue 4 (April 1994) - Godefroy, O; Rousseaux, M; Pruvo, J P; Cabaret, M; Leys, D
Abstract : According to previous studies, focal capsulostriatal lesions may produce aphasia, hemineglect, gestural apraxia, frontal lobe dysfunction, and memory impairment. A few reports of capsulostriate infarcts secondary to involvement of lenticulostriate arteries have confirmed that aphasia and hemineglect may occur whereas gestural apraxia, anosognosia and frontal-lobe symptoms are rare. Most studies used CT scan assessment and did not exclude possible associated lesions. Neuropsychological changes in 11 patients with lenticulostriate infarcts diagnosed by CT scan were prospectively investigated. MRI in five of the 11 patients showed an associated cortical lesion not seen on CT scan. Patients with pure lenticulostriate infarcts on MRI may exhibit aphasia of mild severity whereas Broca's aphasia, hemineglect, gestural apraxia, and anosognosia were only seen in the subgroup with associated cortical lesions. Aphasia in patients with pure lenticulostriate infarcts was characterised by prominent expressive and lexicosemantic task impairments. The results strongly suggest that cortical involvement is critical to the extent and severity of neuropsychological changes in patients with lenticulostriate infarcts.